1998
DOI: 10.1177/0164027598206009
|View full text |Cite
|
Sign up to set email alerts
|

Measuring AIDS-Related Behaviors in Older Populations

Abstract: Because of a dearth of research on reporting biases in the measurement of HIV-related sexual and drug use behaviors in older populations, it is frequently assumed that methodological findings of research conducted with younger populations will generalize to older respondents. In this study, estimates of the effect of the experimental manipulation of interview mode (interviewer administered vs. self-administered) were derived separately for three age strata: 12 to 49, 50 to 64, and 65+. Results of these analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…One clear example of this is the findings referring to the personal interviews, which were inconsistent with the sensitive questions literature that has shown that, because people are required to report sensitive information face-to-face to a third person, PI is usually seen as a weaker measurement mode, which tends to decrease the odds of reporting sensitive behavior (e.g., Gribble et al 1998Gribble et al , 2000. Out of the three experiments considering PI, two studies were developed more than 30 years ago (Krohn et al 1974;Hindelang et al 1981).…”
Section: Modes Of Administrationmentioning
confidence: 81%
See 1 more Smart Citation
“…One clear example of this is the findings referring to the personal interviews, which were inconsistent with the sensitive questions literature that has shown that, because people are required to report sensitive information face-to-face to a third person, PI is usually seen as a weaker measurement mode, which tends to decrease the odds of reporting sensitive behavior (e.g., Gribble et al 1998Gribble et al , 2000. Out of the three experiments considering PI, two studies were developed more than 30 years ago (Krohn et al 1974;Hindelang et al 1981).…”
Section: Modes Of Administrationmentioning
confidence: 81%
“…Research on mode effects is extensive and sometimes yields conflicting results. For example, while some studies found a higher prevalence of drug, cigarette, and alcohol use in self-administered modes (e.g., surveys), compared to other-administered modes (e.g., interviews) (Gribble et al 1998;Gribble et al 2000), others found no significant differences in reports of alcohol use (e.g., Sobell and Sobell 1981) or cigarette smoking (e.g., Moskowitz 2004). Other studies even found higher reports of alcohol use in interviews compared to self-administered modes (Cutler et al 1988;Rehm and Spuhler 1993).…”
Section: Introductionmentioning
confidence: 99%
“…These works include Gribble, Rogers, Miller, and Turner (1998) ;Miller, Gribble, Mazade, Rogers, and Turner (1998) ;Rogers, Miller, and Turner (1998) ;Turner, Danella, and Rogers (1995) ;Turner, Ku, Rogers, Lindberg, Pleck, and Sonestein (1998) ;Turner, Ku, Sonenstein, and Pleck (1996) ;Turner, Miller, and Rogers (1997);and Turner, Miller, Smith, Cooley, and Rogers (1996). With the exception of this statement, we do not note the numerous places where we have drawn on these works.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…In the first half of the 1990's, there was a 53% increase in reported infection through injection in men over 50 and a 75% increase in women over 50 (Hirschhorn, 2001). Despite these trends and concerns, the literature tends to overlook serodiscordant heterosexual couples (VanDevanter, Thacker, Bass, & Arnold, 1999), older injectors (Barnea & Teichman, 1994;Chenitz, Salisbury, & Stone, 1990;Goldmeier, 1994;Gribble, Rogers, Miller & Turner, 1998); and persons over 50 who are living with HIV (Poindexter & Linsk, 2000). The likely consequences of this neglect are inadequate prevention and care.…”
Section: Journal Of Social Work Practice In the Addictionsmentioning
confidence: 99%